Herod's Judaea: a Mediterranean state in the classical world - Rocca, Samuel (Texts and studies in ancient Judaism, 2012)
Hauptbeschreibung: Samuel Rocca presents an in - depth analysis of Herodian society. The most important facet of this analysis was the relationship between Herod as ruler and the Jewish subjects over whom he ruled. Yet to understand the relationship between Herod and his subjects, between ruler and ruled, it is necessary, as part of the general background, to undertake a general analysis of Herodian Judaea and its relationship with the classical world, beginning with Augustan Rome, which was then the center of power, and followed by the main centers within the Mediterranean basin and the Helleni